Effects of NIX‐mediated mitophagy on ox‐LDL‐induced macrophage pyroptosis in atherosclerosis. (27th March 2020) - Peng, Xue; Chen, Hengmei; Li, Yunyun; Huang, Dake; Huang, Baojun; Sun, Dengqun
Abstract: Pyroptosis is a form of cell death that is uniquely dependent on caspase‐1. Pyroptosis involved in oxidized low‐density lipoprotein (ox‐LDL)‐induced human macrophage death through the promotion of caspase‐1 activation is important for the formation of unstable plaques in atherosclerosis. The mitochondrial outer membrane protein NIX directly interacts with microtubule‐associated protein 1 light chain 3 (LC3). Although we previously showed that NIX‐mediated mitochondrial autophagy is involved in the clearance of damaged mitochondria, how NIX contributes to ox‐LDL‐induced macrophage pyroptosis remains unknown. Here, immunoperoxidase staining Nix expression decreased in human atherosclerosis. When we silenced NIX expression in murine macrophage cell, active caspase‐1, and mature interleukin‐1β expression levels were increased and LC3 was reduced. In addition, LDH release and acridine orange and ethidium bromide staining indicated that damage to macrophage cell membranes induced by ox‐LDL was substantially worse. Moreover, intracellular reactive oxygen species and NLRP3 inflammasome levels increased. Taken together, these results demonstrated that NIX inhibits ox‐LDL‐induced macrophage pyroptosis via autophagy in atherosclerosis.